Analysis of Factors Affecting Students' Interest to Save in Sharia Bank: (Case Study Of Students Of Uin Sunan Kalijaga Department of Sharia Banking Class 2019-2021) - Khairunnisa; Rifaatul Indana (Journal of Business Management and Islamic Banking, 2023)
ABSTRACT Research Aims: This study aims to determine whether lifestyle, religiosity, Islamic financial literacy, social environment, and brand image affect students' interest in saving in Islamic banks. This research is quantitative in nature to test the hypotheses that have been set previously. The population of this study are students of UIN Sunan Kalijaga majoring in Islamic banking, class of 2019-2021. Methodology: Sampling from this study using purposive sampling technique. The data in this study were obtained by distributing questionnaires. The primary data in this study uses 85 questionnaires that can be processed. The data analysis method used in this study is multiple linear regression analysis with IBM SPSS 25. Research Findings: The results of this study indicate that simultaneously, the variables of religiosity, social environment, and brand image have a positive and significant effect on the intention to save, while the variables of lifestyle and Islamic financial literacy do not have a significant effect on the interest in saving of students in Islamic banks.